2022
DOI: 10.3390/ijerph20010722
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Therapy Complementary Prehabilitation of Women Diagnosed with Breast Cancer—A Pilot Study

Abstract: Breast cancer is becoming an important issue due to its various consequences and epidemiology. Studies are showing that it extremely impacts the mental health as well as the physical activity of the patients. In addition to the most common symptom, which is fatigue, patients also have problems with the quality of sleep. Therefore, this study aimed to evaluate the effectiveness of virtual reality (VR) therapy in improving the mental state and quality of sleep, as well as increasing the physical activity (PA) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Quality assessments of the randomized studies are presented in Table 2 and are available in Multimedia Appendix 3 . Overall, the risk of bias ranged from low [ 40 ] to some concerns [ 33 , 38 , 39 , 46 , 50 , 51 ] to high [ 34 ]. This assessment depended primarily on knowledge of allocation, number of dropouts, lack of data, and heterogeneity of baseline results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quality assessments of the randomized studies are presented in Table 2 and are available in Multimedia Appendix 3 . Overall, the risk of bias ranged from low [ 40 ] to some concerns [ 33 , 38 , 39 , 46 , 50 , 51 ] to high [ 34 ]. This assessment depended primarily on knowledge of allocation, number of dropouts, lack of data, and heterogeneity of baseline results.…”
Section: Resultsmentioning
confidence: 99%
“…PA levels were assessed in 6 studies using pedometers [ 48 , 50 ], accelerometers and diaries [ 34 ], or questionnaires [ 39 , 46 , 51 ]. Four studies found that AVGs did not significantly improve this parameter [ 34 , 46 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations